Loss of TET proteins in regulatory T cells promotes abnormal proliferation, Foxp3 destabilization and IL-17 expression. (2nd March 2019) - Nakatsukasa, Hiroko; Oda, Mayumi; Yin, Jinghua; Chikuma, Shunsuke; Ito, Minako; Koga-Iizuka, Mana; Someya, Kazue; Kitagawa, Yohko; Ohkura, Naganari; Sakaguchi, Shimon; Koya, Ikuko; Sanosaka, Tsukasa; et al.
Abstract: Ten-eleven translocation (TET) proteins regulate DNA methylation and gene expression by converting 5-methylcytosine (5mC) to 5-hydroxymethylcytosine (5hmC). Although Tet2/Tet3 deficiency has been reported to lead to myeloid cell, B-cell and invariant natural killer T (iNKT) cell malignancy, the effect of TET on regulatory T cells (Tregs) has not been elucidated. We found that Tet2/Tet3 deficiency in Tregs led to lethal hyperproliferation of CD4 + Foxp3 + T cells in the spleen and mesenteric lymph nodes after 5 months of age. Additionally, in aged Treg-specific Tet2/Tet3 -deficient mice, serum IgG1, IgG3, IgM and IgE levels were markedly elevated. High IL-17 expression was observed in both Foxp3 + and Fopx3 - CD4 + T cells, and adoptive transfer of Tet2/Tet3 -deficient Tregs into lymphopenic mice inhibited Foxp3 expression and caused conversion into IL-17-producing cells. However, the conserved non-coding DNA sequence-2 (CNS2) region of the Foxp3 gene locus, which has been shown to be particularly important for stable Foxp3 expression, was only partly methylated. We identified novel TET-dependent demethylation sites in the Foxp3 upstream enhancer, which may contribute to stable Foxp3 expression. Together, these data indicate that Tet2 and Tet3 are involved in Treg stability and immune homeostasis in mice. Abstract : Tet2 and Tet3 are important for Treg proliferation, stability and L-17 expression